47 Progression of preclinical ventricular dysfunction and structural abnormalities in an asymptomatic cohort with elevated natriuretic peptide; a report from the stop-HF project. (16th October 2019) - Ferre, M; Pharithi, RB; Ledwidge, M; Watson, C; McDonald, K; Connell, EO; Gallagher, J
Abstract : Background: Changes in structural and functional cardiac metrics in a high-risk population defined by elevated B-type natriuretic peptide (BNP) remain unclear. Objectives: The purpose of this study was to determine changes in measures of cardiac structure and function, to define clinical phenotype associated with such progression and to determine if BNP change over time predicted progression. Methods: STOP-HF patients with BNP >50pg/ml with 3 sequential echocardiography studies were included. Progression was defined as presence of at least one of the following: left ventricular systolic dysfunction (LVSD) progression (LVEF<50% and reduction of >5% from prior study); left ventricular diastolic dysfunction (LVDD) progression (lateral E/e' >13 and increase of >2 and/or lateral e' <9cm/s with drop of >2cm/s); left atrial volume index (LAVi) progression (LAVi >34 ml/m 2 with 3.5 ml/m 2 increased) and left ventricular mass index (LVMi) progression (>125 g/m 2 male/>110 g/m 2 female, with increase of >20 g/m 2 ). Results: 211 patients were included (median age 69.2 years, 46.9% male). (table 1 ) A total of 129 (61.1%) patients demonstrated progression over a follow up period of 24.7 months. The most common type of progression was LVDD (36.5%). Age, baseline LAVi and lateral e' were the only parameters associated with progression (p<0.05). Neither BNP at baseline or its change over time predicted progression. (Figure 1 ). Conclusion: These data demonstrate a concerning prevalence of deterioration in ventricular structure and function over a short period time in an asymptomatic cohort at heightened cardiovascular risk. The lack of a clear phenotype for this progressor group and in particular the failure for BNP to predict progression underlines the need for further research to best delineate this cohort. Their definition and close clinical follow up may well become necessary if specific therapies become available to attenuate these changes. Progression of preclinical ventricular dysfunction and structural abnormalities in a high risk cohort.